KOMPETENSI PENDIDIK DALAM PEMBELAJARAN BAHASA ARAB - Nuryani, Nuryani (Jurnal Bahasa Lingua Scientia, 2011)
When other foreign language development is creeping to its peak, Arabic language still hasn?t defined its position in the world?s main stream of rapid changing.  Many people ?from students to learners of Arabic language both in formal or non formal institution- haven?t shown their serious effort to put Arabic as a language of science and technology. This condition will stay exactly the same in next period if the Arabic language teaching is not supported by professional and competent Arabic teachers.